Resourceful Civil Society Navigating the Changing Landscapes of Civil Society Organizations - Kravchenko, Zhanna; Kings, Lisa; Jezierska, Katarzyna (Palgrave Studies in Third Sector Research,, 2022)
This open access book examines how civil society organizations in Poland, Russia, and Sweden (re)act to transformations of opportunities and limitations in access to various forms of resources. The volume's contributions discuss the constraints associated with different types of resources as well as organizations' capacities to generate resources-or compensate for their lack-as they negotiate and contest barriers. The resourcefulness of civil society is revealed to be rooted in a variety of capabilities: converting resources, eliciting organizational change, and metamorphosing in response to organizational and environmental development. Zhanna Kravchenko is Associate Professor of Sociology at Södertörn University, Sweden. She has published on various aspects of societal transformation in Russia. Her current research examines the development of civil society, with a particular focus on the role of transnational funding for civilsociety organizations working with human rights and democracy. Lisa Kings is Associate Professor of Social Work at Södertörn University, Sweden. She has conducted extensive empirical and theoretical research in the field of civil society, including urban social movements. Her recent work focuses on action research and connecting academic research to civil society practice. Katarzyna Jezierska is Associate Professor of Political Science at University West, Sweden. Her research interests center on the intersections between civil society and formal politics. She has published on radical democratic subjectivity, think tanks' involvement in policymaking, and the engagement of diplomats with civil society actors .